Analisa Signifikan Kemunculan Pemikiran Feminisme di Indonesia - Halimatus Sa’diyah; Alfin Yulia Nurhidayanti; Wahyu Mashanim M; Octaviona Cinta Dewi; Shifa Salsabila; Emmywati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
Feminist thought is focused on achieving equality between genders in political, social, and economic rights, particularly advocating for women's rights, with the aim of attaining gender equality across all aspects of society. This research utilizes qualitative methods and conducts a literature review, analyzing various books, magazines, and other relevant literature. The objective is to examine how feminism recognizes the unique circumstances that women face in their pursuit of freedom and justice. The research findings and conclusions emphasize the necessity of political support, allocation of human resources, and public participation in the ongoing fight for women's freedom and justice. However, it is evident that significant progress is still required. To address this, the research suggests the need for both vertical democratization of political structures and horizontal democratization to dismantle patriarchal systems.